The Role of The Language Acquisition Device Theory in Second Language Acquisition: A Psycholinguistic Study of Arabic Language Learning - Zikrani Khalilah; Sinta Amalia; Muhammad Gamal Abd Nasser; Sahkholid Nasution; Abdel Rahman ElSayed ElSayed Abdel Ghaffar Balah (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: This study examines the role of the Language Acquisition Device (LAD) theory in second language acquisition within the context of Arabic language learning through a psycholinguistic perspective. Using a descriptive qualitative research method and a literature review approach, this research analyzes various relevant primary and secondary sources. The findings reveal that Noam Chomsky's LAD theory significantly impacts second language acquisition, particularly Arabic. LAD serves as an innate mechanism enabling humans to acquire languages naturally. In the context of Arabic learning, the implementation of LAD theory encompasses three primary factors: motivation, language, and social aspects. Psycholinguistic studies reveal that cognitive processes such as memory and information processing play pivotal roles in acquiring Arabic. This study also found that communicative-based learning approaches, using real-life contexts and social interaction with native speakers, are effective strategies in Arabic language learning. The integration of technology and project-based learning can enrich students' learning experiences. In conclusion, a deeper understanding of LAD theory and its application in Arabic language learning can contribute significantly to the development of more effective teaching methods, enabling students to master Arabic more efficiently in an increasingly complex global context. Keywords: language acquisition device, psycholinguistics, arabic language learning, second language acquisition.